Enhanced approach for developing web applications using model driven architecture - Mukhtar, M.A.O. (2013)
Creating of web application and corresponding information architecture is often associated with social informatics. It clearly lays at the crossing of the ICT and social sciences, especially because effective information architectures enable people to find content quickly, easily and intuitively. Model Driven Architecture (MDA) technique is initiated by the Object Management Group (OMG), based on separation of concerns. It describes the system functionality in platform independent model (PIM) and also describes the implementation of this functionality using platform specific model (PSM), where the transformation process from PIM to PSM is done automatically using QVT model transformation language. To overcome the large scale web application system complexity, model-driven web engineering is used to automate web application using models to describe web site in different abstraction level. The automation in existing web development methods could be enhanced using MDA technique. This paper provides proposed mechanism to enhance Web Site Design Method (WSDM) method by applying MDA technique. The proposed mechanism enhances WSDM from conceptual modeling approach to MDA modeling approach by profiling the conceptual model of WSDM with the new user-interest profile. This redesigned conceptual model is used as PIM model. The proposed mechanism adds generic PSM to the implementation model of WSDM. We use QVT model transformation language to automate the mapping specification from PIM to PSM. Our method is called WSDM using MDA (WSDMDA). Â© 2013 IEEE.